Development of Calligraphy Art in Indonesian Islamic Boarding Schools: Calligraphy Art in Indonesian Islamic Boarding Schools - Madina, Ahsani Madina; Endang Erika; Dharma Syahputra; Amin Agung Sasmito; Sahkholid Nasution (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Islamic boarding schools are known to the public because many of the students' works are introduced through culture and religion so that these works are known to the outside community. In Islamic boarding schools, students are also taught to study religious knowledge and deepen it in an effort to create a generation whose character is formed in accordance with Islamic law. So it is no longer surprising to find Islamic boarding school alumni who have good scientific character. If you find a work of calligraphy art in a shop, what comes to mind is that this work is one of the works of Islamic boarding school children. So that it attracts the attention of parents to enroll their children in Islamic boarding schools because of the works created by these students. The developments that can be seen at this time are the many impacts of the influence of calligraphy in Islamic boarding schools and outside Islamic boarding schools. The impact of the art of calligraphy has had an influence on the development of Islam. The purpose of writing this article is to find out about the art of calligraphy in Islamic boarding schools. In this research, the author used a descriptive qualitative method through a literature study approach, taking reference material from journals, books, articles, and others, as mandatory material for this research.